The Effect Of Absolute Strength Training On Knee Injuries Rehabilitation And Special Strength In Muay Thai Fighters - Masaier, Ali (Journal of Physical Education, 2019)
The importance of the research lies in the increase number of knee injuries in sports and the necessity of correctly treating it and rehabilitating it especially for Muay Thai fighters. The problem of the research lies in designing a training program for treating and rehabilitating knee and ankle injuries including absolute strength exercises for working muscles in these joint after surgery. The researcher applied the training program on Muay Thai fighters' injuries during the season 20014 – 2015. The program lasted for eight weeks with three training sessions per week. The researchers concluded that diagnosing injury and the degree of pain contribute in muscle effort placed on it as well as strengthening muscle power of muscles around joints increase their efficiency after rehabilitation. Finlay the researcher concluded that the training program lead to the development of the maximum strength of knee and ankle muscles.